2000
DOI: 10.1037/0012-1649.36.6.793
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative risk and early cognitive development: A comparison of statistical risk models.

Abstract: Although it is generally accepted that social risk factors predict delays in early cognitive and language development, there is less agreement about how to represent such associations statistically. Using data collected prospectively on 87 African American children during their first 4 years, this study examined 3 analytic methods for describing a child's level of social risk: (a) individual risk variables, (b) factor scores derived from those risk variables, and (c) a risk index computed by tallying the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
232
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(252 citation statements)
references
References 39 publications
10
232
0
7
Order By: Relevance
“…Each risk factor represents whether the family met some risk criterion on a risk variable, but these risk variables are almost always related in an approximately linear, not stepwise, manner with outcomes of interest such as parenting or child outcomes. For example, outcomes tend to be poorer when mothers have less than a high school education, but the number of years of maternal education is a stronger predictor of parenting and child outcomes than the categorized indictor of high school graduation (Burchinal et al, 2000). In addition, the risk index computed as the sum of risk factors can have only a relatively few possible values (i.e., the maximum is one more than the number of risk factors examined), whereas the mean of the risk variables can assume many more values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Each risk factor represents whether the family met some risk criterion on a risk variable, but these risk variables are almost always related in an approximately linear, not stepwise, manner with outcomes of interest such as parenting or child outcomes. For example, outcomes tend to be poorer when mothers have less than a high school education, but the number of years of maternal education is a stronger predictor of parenting and child outcomes than the categorized indictor of high school graduation (Burchinal et al, 2000). In addition, the risk index computed as the sum of risk factors can have only a relatively few possible values (i.e., the maximum is one more than the number of risk factors examined), whereas the mean of the risk variables can assume many more values.…”
Section: Discussionmentioning
confidence: 99%
“…Although counting number of risk factors was more typical, the use of risk composites based on continuous risk variables is becoming more common because it retains more information in the individual risk factors and, thereby, increases power for detecting the interactions necessary to identify protective factors (Burchinal et al, 2000;Deater-Deckard et al, 1998). A factor analysis indicated that a single factor accounted for 38% of the variance in the 7 risk variables and that each risk variable at least partially loaded on the first factor (.24 < loading < .80).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…365 It is now well documented that environmental factors such as maltreatment, family adversity, marital conflict, maternal depression, and even financial distress are been linked with cognitive deficits and socio-emotional behavioral problems in children. [366][367][368][369][370][371][372][373][374][375][376][377][378][379] The mechanism of such biological embedding has been called "time dependent sensitization," 380 "neural sensitization," 381 "sensory hyper-arousal," 382 "central sensitization," 383 "central nervous system sensitization," 384 and "sensitivity to context," 385 but by any name, they reflect the self-regulatory feedback dynamics-and epigenetic and immune manifestations-of the emotional sense.…”
Section: Original Articlementioning
confidence: 99%